Not just avoidance: dogs show subtle individual differences in reacting to human fear chemosignals - Capitain, Svenja; Range, Friederike; Marshall-Pescini, Sarah (Frontiers in Veterinary Science, 2025)
Recent olfactory studies suggest that human emotional chemosignals can alter dog behavior. However, their methods impeded a firm conclusion on whether dogs reacted to the scent directly or to the present human’s unconscious response to the intraspecific stimulus. Moreover, whether these reactions differ between dogs has not yet been explored. Therefore, we investigated dogs’ reactions to human fear or neutral chemosignals while shielding the present human from the smells. Dogs were first trained to approach a single empty target on command, before they were given the choice between two targets laced with human smell (experimental group (n = 41): one fear target and one neutral; control group (n = 20): both neutral targets). Dogs in the experimental group stayed longer with the experimenter, displayed lower tail posture, and took longer to approach a target than control dogs, though target choice did not differ at the group level. Age and sex showed no effect. Furthermore, dogs in the experimental group compared to the control group showed stronger interindividual variation in how quickly they approached one smell over the other and how many commands they required. This finding suggests that dogs are indeed influenced by human fear smell beyond the humans’ reaction, though it challenges previous assumptions of an innate interspecific fear avoidance. The influence of life experience or breed on the individual differences may be worth exploring to better understand and guide dogs’ experience of the world.